2020
DOI: 10.1093/cdn/nzaa113
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Characterization and Longitudinal Study Reveal Distinguishing Features of Human Milk Oligosaccharides in China

Abstract: Abstract Background Human milk oligosaccharides (HMOs) in breast milk contribute to the development of neonatal microbiota and immune system. However, longitudinal studies examining HMOs profiles of Chinese mothers remain scarce. Objective To analyze HMOs profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
8
21
2
Order By: Relevance
“…The HMO intake ranged from 2.6 ± 0.79 g/day at V1 to 5.2 ± 0.7 g/day at V6, showing only a slight increase after 4 weeks. The total HMO concentration and the ratio of the HMOs in the formula remained constant during the intervention period, whereas in breast milk the concentration of several HMOs decreases within the first few months after delivery [ 40 ], while a few HMOs, such as 3-FL, become more abundant [ 29 , 40 ]. The absolute concentration of different HMOs is primarily influenced by the mother’s Secretor status but also by her BMI and diet as well as several other factors described above [ 40 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HMO intake ranged from 2.6 ± 0.79 g/day at V1 to 5.2 ± 0.7 g/day at V6, showing only a slight increase after 4 weeks. The total HMO concentration and the ratio of the HMOs in the formula remained constant during the intervention period, whereas in breast milk the concentration of several HMOs decreases within the first few months after delivery [ 40 ], while a few HMOs, such as 3-FL, become more abundant [ 29 , 40 ]. The absolute concentration of different HMOs is primarily influenced by the mother’s Secretor status but also by her BMI and diet as well as several other factors described above [ 40 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total HMO concentration and the ratio of the HMOs in the formula remained constant during the intervention period, whereas in breast milk the concentration of several HMOs decreases within the first few months after delivery [ 40 ], while a few HMOs, such as 3-FL, become more abundant [ 29 , 40 ]. The absolute concentration of different HMOs is primarily influenced by the mother’s Secretor status but also by her BMI and diet as well as several other factors described above [ 40 , 61 ]. The overall concentration of HMOs declines from 20–25 g/L in the colostrum to 10–15 g/L in mature milk ([ 33 , 34 ] and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of HMOs in human milk is also dependent on genetic factors, including secretor and Lewis blood status of women ( Table 1 ) ( 21 , 22 ). The secretor gene ( Se ) encodes an α1-2-fucosyltransferase (FUT2), and the Lewis gene ( Le ) encodes an α1-3/4-fucosyltransferase (FUT3), allowing the fucosylation of HMOs.…”
Section: Structure Of Hmos and Their Compartmentalization In Mothers And Childrenmentioning
confidence: 99%
“…Obviously, the analysis of the absolute HMO content does not give detailed information about the change of individual HMOs with regard to different factors. To address such questions, a good number of studies have therefore focused on the quantification of the most important milk sugars [ 7 , 12 , 17 , 20 , 28 , 29 , 42 , 43 , 46 , 47 , 48 ]. These have for instance shown that 3FL increases up to almost threefold throughout the course of lactation regardless of the milk status and gestational age [ 7 , 12 , 17 , 28 , 29 , 32 , 43 , 47 , 48 ].…”
Section: Structure Of Human Milk Oligosaccharides and Human Milk Cmentioning
confidence: 99%